Safety of Antitheilerial Drug Buparvaquone in Rams - Isik, Nermin; Ekici, Ozlem Derinbay; Ilhan, Ceylan; Coskun, Devran (Acta Scientiae Veterinariae, 2018)
Background: Theileriosis is a tick-borne disease caused by Theileria strains of the protozoan species. Buparvaquone is the mostly preferred drug in the treatment theileriosis, while it is safety in sheep, has not been detailed investigated. It has been hypothesized that buparvaquone may show side effects and these effects may be defined some parameters measured from blood in sheep when it is used at the recommended dose and duration. The aim of this research was to determine the effect of buparvaquone on the blood oxidative status, cardiac, hepatic and renal damage and bone marrow function markers. Materials, Methods & Results: In this study, ten adult (> 2 years) Akkaraman rams were used. Healthy rams were placed in paddocks, provided water ad libitum, and fed with appropriate rations during the experiment. Buparvaquone was administered at the dose of 2.5 mg/kg (IM) intramuscularly twice at 3-day intervals. Blood samples were obtained before (0. h, Control) and after drug administration at 0.25, 0.5, 1, 2, 3, 4 and 5 days. The blood samples were transferred to gel tubes, and the sera were removed (2000 g, 15 min). During the study, the heart rate, respiratory rate, and body temperature were measured at each sampling time. In addition, the animals were clinically observed. Plasma oxidative status markers (Malondialdehyde, total antioxidant status, catalase, glutathione peroxidase, superoxide dismutase), serum cardiac (Troponin I, creatine kinase-MBmass, lactate dehydrogenase), hepatic (Alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, gamma glutamyltransferase, total protein, albumin, globulin) and renal (Creatinine, blood urea nitrogen) damage markers and hemogram values (white blood cell, red blood cell, platelet, hemogram, hematocrit) were measured. Buparvaquone caused statistically significantly (P < 0.05) increases in the troponin I and blood urea nitrogen levels and fluctuations in alkaline phosphatase activity, but there was no any statistically significance difference determined in the other parameters. Discussion: In this study, buparvaquone was administered two times at a dose of 2.5 mg/kg (IM) at 3-day intervals. Although the result was not statistically significant (P > 0.05), it was determined that buparvaquone gradually increased the levels of the main oxidative stress marker, MDA, by approximately 2.8 fold. CAT and GPX levels were also found to have decreased by 2.2 fold. Buparvaquone may cause lipid peroxidation by producing free radicals. Some other antiprotozoal drugs may affect the oxidative status and may increase MDA level and decrease SOD level. In this study, MDA, which is an indicator of lipid peroxidation in vivo, was used to partially detect developing lipid peroxidation. Changes in the levels of reduced GPX and CAT enzymes could be attributed to their use in mediating the hydrogen peroxide detoxification mechanisms. The absence of significant changes in the TAS levels in this study suggests that buparvaquone may partially induce oxidative stress by producing hydrogen peroxide, but no significant changes occurred in the oxidative stress level because of the high antioxidant capacity of sheep. In this study, buparvaquone caused a statistically significant increase (P < 0.05) in the level of Tn-I, which is a marker of specific cardiac damage (P < 0.05), whereas there was no statistically (P > 0.05) significant increase in CK-MBmass. Tn-I and CK-MB levels, which are used to define heart damage in humans, have been successfully used to determine heart damage in sheep. In this research study, the statistically significant increases in Tn-I but not CK-MBmass levels could be considered indicative of mild cardiac damage.